PENYIDIKAN TINDAK PIDANA PENCURIAN KELAPA SAWIT DI WILAYAH KEPOLISIAN SEKTOR SOSA KABUPATEN PADANG LAWAS PROVINSI SUMATERA UTARA - Hasan Azhari Lubis; Erdianto '; Lady Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The development of oil palm plantations not only thrive in big cities but also developing dikecamatan-districts in North Sumatra and the surrounding areas. Sosa is a district in North Sumatra Padang Lawas regency, that generally, people familiar with Sosa as cypress oil palm plantation area. Sosa has occurred in the district of palm oil theft were 41 cases with 73 suspects from the period of 2010 - in 2014. From lataer the back of pick-authors are interested in these issues in a scientific study. The research objective of this thesis: First, to determine the investigation of criminal theft of palm oil in the Police Sector Sosa Padang Lawas regency of North Sumatra Province. Second, to determine the obstacles faced in the investigation of criminal theft of oil palm in the Police Sector Sosa Padang Lawas regency of North Sumatra Province. Third, To know the efforts made.From the research, there are three main things that can disumpulkan. First, the investigation process is not running optimally because people still recognize indigenous settlement that does not have a strict sanctions. In addition to the habits of the people who do not want to report on and assume the process dikepolisian rambling and very long. Second, the existence of two inhibiting factors, namely internal factors and external factors. Such constraints include: lack of personnel, cultural / community customs, lack of funds and infrastructure. Third, To Overcome obstacles do undertakings addition of personnel, premises cooperating parties palm oil companies and communities Sosa and minimize the use of funds and utilize existing infrastructure.Suggestions author is the Police Sector should be more synergy Sosa and must firmly move quickly in tackling and prosecuting those responsible for the crime of theft of oil palm. Society must be cooperative in reporting and for palm oil businessmen in order to carry out the advice given by the Police Sector Sosa to set up security posts and also installing portals at certain points that are considered vulnerable.Keywords: Investigation - Crime - Theft - Palm Oil - Police Sector Sosa